2021
DOI: 10.3390/mi12080910
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Lapping Process Parameters for Single-Crystal 4H–SiC Using Orthogonal Experiments and Grey Relational Analysis

Abstract: Lapping is one of the standard essential methods to realise the global planarization of SiC and other semiconductor substrates. It is necessary to deeply study the mechanism to obtain SiC lapping process parameters with a strong comprehensive lapping performance (i.e., high material removal rate (MRRm), small surface roughness (Ra), and low total thickness variation (TTV)). The effects of the lapping process parameters and their interactions on lapping performance for SiC were investigated using orthogonal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…For example, stainless steel polishing [13], light guide plate laser cutting [16], green sand mold system [17], steel turning [18], EN 8 material grinding [19], aluminum alloy cutting [20], and other aspects have been optimized using the grey relational analysis method, achieving a relatively ideal combination of parameters, and saving substantial experimental cost. Deng et al [21] applied the grey relational analysis method to the 4 H-SiC lapping process and finally achieved an MRR of 90.2 µm h −1 , and a surface roughness Ra of 0.769 nm. The study demonstrated that combining orthogonal experiments and grey relational analysis can provide novel insights for optimizing the silicon carbide process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, stainless steel polishing [13], light guide plate laser cutting [16], green sand mold system [17], steel turning [18], EN 8 material grinding [19], aluminum alloy cutting [20], and other aspects have been optimized using the grey relational analysis method, achieving a relatively ideal combination of parameters, and saving substantial experimental cost. Deng et al [21] applied the grey relational analysis method to the 4 H-SiC lapping process and finally achieved an MRR of 90.2 µm h −1 , and a surface roughness Ra of 0.769 nm. The study demonstrated that combining orthogonal experiments and grey relational analysis can provide novel insights for optimizing the silicon carbide process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…3.2 GRA GRA was introduced in 1982 by J. L. Deng and is one of the sub-titles of systems theory (Deng et al, 2021). In control theory, colors are often used to show the clarity of information.…”
Section: Methodsmentioning
confidence: 99%
“…GRA was introduced in 1982 by J. L. Deng and is one of the sub-titles of systems theory (Deng et al. , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As regards semiconductor development, silicon carbide (SiC) materials are currently known to exhibit excellent material advantages such as high forbidden bandwidth, high thermal conductivity, and high electron migration rate as compared with silicon materials [1][2][3][4]. Therefore, SiC devices are being widely used in various fields such as new energy-efficient vehicles, smart grids, and aerospace applications [5][6][7].…”
Section: Introductionmentioning
confidence: 99%